Student Mistakes in Solving Math Story Problems (Class V Study at SDN Sedatigede I Sidoarjo) - Sumartono (Asian Journal of Applied Education (AJAE), 2023)
In working on word problems in mathematics, students often find answers that are not quite right. The purpose of this research is to describe the pattern of errors when working on math story problems, the factors that cause work errors, and alternative learning solutions to minimize student errors in solving word problems. Research data collection techniques used math tests in the form of story questions and student interviews. Factors that cause students' mistakes in solving math word problems, are the lack of mastery of mathematical concepts and understanding of problems in story problems, students' learning methods are not organized (not every day), they are lacking in doing exercises especially story problems, working on easy questions Of course, if you have difficulty don't ask directly to the teacher or friends who can (students choose to be silent), are not careful in carrying out calculations (addition, subtraction, multiplication and division operations), don't pay close attention to question orders, don't carry out the procedures used to solve problems. story problems and lack of mastery of material concepts related to story problems.